Seni Sebagai Media Konseling: Integrasi Pembelajaran Seni Budaya dan Bimbingan Konseling dalam Pengembangan Karakter Siswa - Kusuma, I Dewa Gede Raja Wijaya; Wiguna, Ida Bagus Alit Arta; Widiary, Ni Putu Eka; Karyasa, Teguh; Suardika, I Putu; Pratama, I Putu Gede Aditya Pratama (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
Integrating arts and culture learning and counseling in students' character development at SMKN 5 Mataram. This research explores how art can serve as a counseling medium to help students overcome emotional and social problems and develop character. The method used was a qualitative approach with a case study involving in-depth interviews, classroom observation, and documentation. The research findings show that cultural arts, such as drawing and dance, allow students to express their feelings more openly and reduce anxiety, improving their character in responsibility, cooperation, and self-control. The contribution of this study is to show that arts are beneficial in the context of creative expression and as an effective tool in counseling for character development in vocational high schools. These results are important because they provide new insights into using art in character education and counseling that can be applied in various schools.